Polyolefin microporous membrane
Patent Information
- Application Number
- JP2025061936
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
【0011】 本発明によれば、高突刺強度、高透過性及び低熱収縮性を高度に兼ね備えたポリオレフィン微多孔膜、その製造方法、及びそれを用いた電気化学デバイス用セパレータを提供することができ、さらにそのセパレータを電気化学デバイスに用いれば、薄膜でも機械強度を確保できるため高エネルギー密度が得られるとともに、高入出力密度と高温での寸法安定性に優れた高安全性との高度な両立を達成することができる。
Smart Images

Figure 2026168656000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to polyolefin microporous membranes and the like. [Background technology]
[0002] Polyolefin microporous membranes (hereinafter sometimes simply abbreviated as "PO microporous membranes") are widely used for the separation of various substances, or as selective permeable separation membranes, isolation materials, etc. Their applications include, for example, microfiltration membranes; separators for batteries such as lithium-ion batteries and fuel cells; separators for capacitors; and base materials for functional membranes that allow functional materials to be filled into the pores to create new functions. Among these, PO microporous membranes are particularly suitable as separators for lithium-ion batteries (LIBs), which are widely used in mobile phones, smartphones, wearable devices, notebook personal computers (PCs), tablet PCs, digital cameras, and the like.
[0003] In recent years, the applications of LIB-equipped devices have expanded, and the required performance has become broader and more sophisticated, including miniaturization / thinning, rapid charging capability, and durability. LIBs are therefore required to have high energy density, high input / output density, and high safety. To achieve higher energy density in batteries, separators are being made thinner. However, simply thinning conventional films reduces the mechanical strength of the separator, leading to increased short-circuit failures during battery assembly, reduced yield, and difficulty in ensuring battery safety. Therefore, improved mechanical strength, i.e., puncture resistance, is required. On the other hand, high permeability of the separator is also necessary for high input / output density in batteries, but simply increasing the porosity of the film reduces film strength. Furthermore, from a safety perspective, for high-temperature characteristics, PO microporous films must possess dimensional stability (low thermal shrinkage performance) at high temperatures to be used as LIB separators. To achieve both of the above separator properties, various PO microporous films and their manufacturing methods have been proposed.
[0004] For example, Patent Document 1 discloses a PO microporous membrane that satisfies specific DSC indicators, using polyethylene (PE) and polypropylene as raw materials, either single or blended, with viscosity-average molecular weight (Mv) of 250,000 to 2,500,000, from the viewpoint of high strength, low thermal shrinkage, and high permeability, in order to achieve both safety in impact tests and oven tests of electrochemical devices.
[0005] Patent Document 2 discloses a PO microporous membrane that satisfies specific crystallinity indicators, or is obtained by supplying a mixed slurry to an extrusion process, using raw materials that are a blend of PE with an Mv of 2,500,000 or 4,500,000 and high-density polyethylene and / or polypropylene, from the viewpoint of high quality, high strength and compressibility of the PO microporous membrane. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] International Publication No. 2020 / 256138 [Patent Document 2] Japanese Patent Publication No. 2023-120223 [Overview of the project] [Problems that the invention aims to solve]
[0007] In the field of microporous membranes, it is known that ultra-high molecular weight polyethylene (so-called UHMWPE) with an Mv exceeding 1,000,000 is difficult to mold. The methods described in Patent Document 1 or 2 achieve a balance of high strength, low thermal shrinkage, and high permeability by using PO microporous membranes that meet specific indicators using blended raw materials and manufacturing methods. However, for LIB separators, a higher level of balance between high puncture strength, high permeability, and low thermal shrinkage is required, and there was room for further improvement from that perspective.
[0008] In view of the above circumstances, the present invention aims to provide a polyolefin microporous membrane that combines high puncture strength, high permeability, and low thermal shrinkage, a method for producing the same, and a separator for electrochemical devices and an electrochemical device using the same. [Means for solving the problem]
[0009] As a result of diligent research, the inventors of the present invention have found that the above problems can be solved by controlling the viscosity-average molecular weight (Mv), average pore size, and indicators measured by thermomechanical analysis (TMA) within a specific range in a polyolefin microporous membrane mainly composed of polyethylene, and have completed the present invention. Examples of embodiments of the present invention are listed below. (1) A polyolefin microporous membrane containing polyethylene as the main component, The viscosity-average molecular weight (Mv) of the polyolefin microporous membrane is between 1,200,000 and 9,000,000. The average pore size measured according to the half-dry method for the aforementioned polyolefin microporous membrane is 0.020 μm or more and 0.100 μm or less, and The shrinkage stress S at 140°C was measured by the shrinkage stress mode in thermomechanical analysis (TMA) of the aforementioned polyolefin microporous membrane. 140 And, the maximum shrinkage stress S at temperatures above 140°C max A polyolefin microporous membrane in which the stress gradient A, calculated from the two points, is between 0.030 and 0.070. (2) The polyolefin microporous membrane according to item 1, wherein, in the molecular weight distribution curve of the polyolefin microporous membrane obtained from gel permeation chromatography (GPC) measurement, the ratio of components with a molecular weight of 300,000 or less to the total molecular weight components is 10% by mass or more and 45% by mass or less, and the ratio of components with a molecular weight of 3,000,000 or more is 2% by mass or more and 30% by mass or less. (3) The maximum shrinkage stress S at temperatures above 140°C, as measured by the shrinkage stress mode in thermomechanical analysis (TMA) of the polyolefin microporous membrane. max 2.0 N / mm 2 The following is a polyolefin microporous membrane as described in item 1 or 2. (4) Shrinkage stress S at 100°C, measured by the shrinkage stress mode in MD of thermomechanical analysis (TMA) of the polyolefin microporous membrane. 100 And, the shrinkage stress S at 120°C 120 A polyolefin microporous membrane described in any one of items 1 to 3, wherein the stress gradient B calculated from the two points is between -0.010 and 0.010. (5) A polyolefin microporous membrane according to any one of items 1 to 4, wherein the film rupture temperature, as measured by the shrinkage stress mode in thermomechanical analysis (TMA) of the polyolefin microporous membrane, is 150°C or higher and 240°C or lower. (6) The polyolefin microporous membrane according to any one of items 1 to 5, wherein the porosity of the polyolefin microporous membrane is 20% or more and 50% or less. (7) The MD tensile breaking strength and TD tensile breaking strength of the polyolefin microporous membrane are both 2000 kgf / cm². 2 The above is a polyolefin microporous membrane as described in any one of items 1 to 6. (8) The polyolefin microporous membrane according to any one of items 1 to 7, wherein the ratio of the MD tensile breaking strength to the TD tensile breaking strength (MD strength / TD strength) of the polyolefin microporous membrane is 0.3 or more and 3.0 or less. (9) The polyolefin microporous membrane according to any one of items 1 to 8, wherein the thickness of the polyolefin microporous membrane is 10 μm or less. (10) A separator for electrochemical devices comprising a polyolefin microporous membrane as described in any one of items 1 to 9. (11) An electrochemical device including a separator for an electrochemical device as described in item 10.
[0010] Examples of other embodiments of this disclosure are listed below. (12) A mixing step (a) involves mixing a resin composition containing a polyolefin resin and a pore-forming material, The mixture obtained in step (a) is melted and kneaded and then extruded in extrusion step (b), The sheet forming process (c) involves forming the extruded material obtained in process (b) into a sheet, The sheet-like molded product obtained in step (c) is stretched at least once in at least one axial direction in a primary stretching step (d), Extraction step (e) is performed to extract the pore-forming material from the primary stretched film obtained in step (d), The heat-fixing step (f) involves heat-fixing (HS) the extracted film obtained in step (e). A method for producing a polyolefin microporous membrane containing, A method for producing a polyolefin microporous film, characterized in that step (a) includes a process of atomizing the polyolefin resin either alone or, if the pore-forming material is a liquid plasticizer, in a mixed state with the liquid plasticizer. (13) A method for producing a polyolefin microporous membrane according to item 12, wherein the polyolefin resin contains ultra-high molecular weight polyethylene. (14) In step (d), the sheet-like molded material is stretched to MD and TD. After step (e), the extracted film is thermally fixed to TD in step (f). A method for producing a polyolefin microporous membrane as described in item 12 or 13. [Effects of the Invention]
[0011] According to the present invention, it is possible to provide a polyolefin microporous membrane that highly combines high puncture strength, high permeability, and low thermal shrinkage, a method for producing the same, and a separator for electrochemical devices using the same. Furthermore, if the separator is used in an electrochemical device, high energy density can be obtained because mechanical strength can be ensured even in a thin film, and a high degree of compatibility between high input / output density and high safety with excellent dimensional stability at high temperatures can be achieved. [Brief explanation of the drawing]
[0012] [Figure 1] This is a schematic diagram showing the measurement results of shrinkage stress at MD for TMA in Example 1. [Figure 2] This is a schematic diagram showing the measurement results of shrinkage stress at MD for TMA in Comparative Example 1. [Modes for carrying out the invention]
[0013] Hereinafter, the modes for carrying out the present invention (hereinafter sometimes abbreviated as "the present embodiment") will be described in detail, but the present invention is not limited thereto, and various modifications are possible without departing from the gist thereof. In this specification, the flow direction of the membrane during film formation is defined as MD, and the direction intersecting MD at 90 degrees in the membrane plane is defined as TD.
[0014] The polyolefin microporous membrane (PO microporous membrane) according to the present embodiment contains polyethylene (PE) as a main component, and has the properties shown below with respect to the viscosity average molecular weight (Mv), the average pore size measured in accordance with the half-dry method, and the shrinkage stress measured by thermomechanical analysis (TMA).
[0015] If desired, the PO microporous membrane can also be specified in terms of membrane thickness, thermal shrinkage rate, porosity, air permeability, puncture strength and the like as shown below, and an inorganic coating layer or an adhesive layer can also be formed on the surface thereof. The plurality of properties described in the present embodiment can be utilized independently of each other or can be arbitrarily combined. Unless otherwise specified, the methods for measuring the physical properties of the PO microporous membrane will be described in detail in the section of Examples.
[0016] <Viscosity average molecular weight of PO microporous membrane> The viscosity average molecular weight (Mv) of the PO microporous membrane according to the present embodiment is 1,200,000 or more and 9,000,000 or less. As the molecular weight of the PO microporous membrane itself increases, the polymers constituting the PO microporous membrane become entangled with each other, so that the membrane has high puncture strength, the separator tends to be able to be made thinner, and when the membrane melts upon reaching a high temperature, the resin does not flow out due to high viscosity, and by retaining its form, the insulating function is secured, and thermal runaway tends to be easily suppressed. From such a viewpoint, the Mv of the PO microporous membrane is preferably 1,300,000 or more, more preferably 1,400,000 or more, still more preferably 1,500,000 or more, even more preferably 1,600,000 or more, particularly preferably 1,700,000 or more, and most preferably 1,800,000 or more. On the other hand, from the viewpoint of suppressing thermal shrinkage of the PO microporous membrane, as well as from the viewpoint of ensuring quality such as gel suppression and membrane uniformity, the Mv of the PO microporous membrane is preferably 8,000,000 or less, more preferably 7,000,000 or less, still more preferably 6,000,000 or less, even more preferably 5,000,000 or less, particularly preferably 4,000,000 or less, remarkably preferably 3,500,000 or less, and most preferably 3,000,000 or less.
[0017] In the present specification, the viscosity average molecular weight of the PO microporous membrane is obtained by measuring the Mv of the PO microporous membrane itself. The viscosity average molecular weight of the PO microporous membrane can be adjusted to the above range by, for example, changing the composition ratio of raw material polymers having different molecular weights.
[0018] <Weight average molecular weight, number average molecular weight, and molecular weight distribution of PO microporous membrane> From the viewpoint of obtaining a separator that ensures high safety while maintaining mechanical strength even in a thin film, the weight-average molecular weight (Mw) of the PO microporous membrane is preferably 800,000 or more, more preferably 900,000 or more, even more preferably 1,000,000 or more, even more preferably 1,100,000 or more, particularly preferably 1,200,000 or more, and most preferably 1,300,000 or more, which increases strength and melt viscosity. On the other hand, from the viewpoint of obtaining a separator with low thermal shrinkage and high quality, the Mw of the PO microporous membrane is preferably 5,000,000 or less, more preferably 4,000,000 or less, even more preferably 3,000,000 or less, even more preferably 2,000,000 or less, and particularly preferably 1,500,000 or less.
[0019] The value obtained by dividing the weight-average molecular weight (Mw) of a PO microporous membrane by its number-average molecular weight (Mn) (Mw / Mn) is preferably 2.0 or higher, more preferably 2.5 or higher, even more preferably 3.0 or higher, even more preferably 3.5 or higher, particularly preferably 4.0 or higher, and even more preferably 5.0 or higher, from the viewpoint of maintaining appropriate molecular entanglement and obtaining good film formation stability. On the other hand, from the viewpoint of ensuring good film formation, productivity, and thin film formation, Mw / Mn is preferably 20.0 or lower, more preferably 18.0 or lower, even more preferably 16.0 or lower, even more preferably 14.0 or lower, particularly preferably 12.0 or lower, and most preferably 10.0 or lower. Note that the weight-average molecular weight (Mw), number-average molecular weight (Mn), and Mw / Mn of the PO microporous membrane in this disclosure are molecular weights in polyethylene equivalent obtained by gel permeation chromatography (GPC) measurement.
[0020] In this embodiment, in the molecular weight distribution curve of the PO microporous membrane obtained from gel permeation chromatography (GPC) measurement performed according to the measurement method in the examples described later, it is preferable that the ratio of components with a molecular weight of 300,000 or less to the total molecular weight components is 10% by mass or more and 45% by mass or less, and the ratio of components with a molecular weight of 3,000,000 or more is 2% by mass or more and 30% by mass or less. From the viewpoint of achieving both high puncture strength, high permeability and high membrane uniformity, the ratio of components with a molecular weight of 300,000 or less to the total molecular weight components is more preferably 15% by mass or more and 42% by mass or less, even more preferably 20% by mass or more and 40% by mass or less, and even more preferably 25% by mass or more and 38% by mass or less. In the above molecular weight distribution curve, from the viewpoint of achieving a high balance between high puncture strength, high permeability and low thermal shrinkage, it is more preferably 4% by mass or more and 20% by mass or less, even more preferably 6% by mass or more and 15% by mass or less, and even more preferably 8% by mass or more and 12% by mass or less.
[0021] In this specification, the weight-average molecular weight, number-average molecular weight, and molecular weight distribution of a PO microporous membrane are obtained by measuring the Mw, Mw / Mn, and molecular weight distribution of the PO microporous membrane itself. The Mw, Mw / Mn, and molecular weight distribution of the PO microporous membrane can be adjusted to the above ranges, for example, by changing the composition ratio of raw material polymers with different molecular weights.
[0022] <pore diameter> The pore size of the PO microporous membrane according to the present embodiment is 0.020 μm or more and 0.100 μm or less. In the present specification, the pore size of the PO microporous membrane means an average pore size measured using a palm porometer (Porous Materials, Inc.: CFP-1500AE) in accordance with the half-dry method. From the viewpoint of ensuring the permeability of the PO microporous membrane, and from the viewpoint of ensuring cycle characteristics by suppressing clogging and ensuring gas release properties when mounted in an electrochemical device as a separator, the pore size of the PO microporous membrane is preferably 0.023 μm or more, more preferably 0.026 μm or more, still more preferably 0.028 μm or more, even more preferably 0.030 μm or more, particularly preferably 0.032 μm or more, and most preferably 0.034 μm or more. On the other hand, from the viewpoint of ensuring high strength of the PO microporous membrane, and from the viewpoint of ensuring cycle characteristics by suppressing clogging due to foreign matter contamination when mounted in an electrochemical device as a separator and ensuring the uniformity of lithium ion ingress and egress on the electrode, the pore size of the PO microporous membrane is preferably 0.090 μm or less, more preferably 0.080 μm or less, still more preferably 0.070 μm or less, even more preferably 0.060 μm or less, particularly preferably 0.050 μm or less, remarkably preferably 0.045 μm or less, and most preferably 0.040 μm or less.
[0023] As means for controlling the pore size of the PO microporous membrane within the above numerical range, for example, in the method for producing a PO microporous membrane described later, adjusting the Mv of the PE raw material described later, performing a fine granulation treatment, adjusting the stretching areal magnification and / or stretching temperature, adopting simultaneous biaxial stretching, performing the stretching step before the extraction step; adjusting the total stretching magnification of the resin molded product; during the heat setting (HS) step, adjusting the HS stretching temperature and HS relaxation temperature, adjusting to satisfy HS stretching temperature < HS relaxation temperature, adjusting the HS stretching magnification, adjusting the HS relaxation magnification, and the like can be used alone or in appropriate combination.
[0024] <Properties measured by thermomechanical analysis (TMA)> In the PO microporous membrane according to the present embodiment, the shrinkage stress S at 140°C measured by the shrinkage stress mode in MD by thermomechanical analysis (TMA)140 and the maximum shrinkage stress S above 140°C max , the value of stress gradient A calculated from the two points is 0.030 or more and 0.070 or less.
[0025] The PO microporous membrane in the present embodiment contains polyethylene as a main component. For example, high-density polyethylene has a melting point around 130°C to 145°C, and polyethylene highly oriented in the stretching axis direction may have its melting point shifted to a higher temperature as compared with non-oriented polyethylene. The strain during stretching is frozen as residual stress inside the stretched PO microporous membrane. When the PO microporous membrane of the present embodiment is measured in the shrinkage stress mode in the MD of TMA, as shown in Example 1 (Figure 1), when the temperature is swept in the heating direction at a constant displacement, internal stress starts to be generated as the membrane attempts to shrink at around 70°C to 80°C, an inflection point appears at around 140°C, then the temperature at which the maximum shrinkage stress is exhibited is reached, and as the temperature approaches the melting temperature, the membrane softens and flows, rapidly elongates, and finally exhibits a behavior of breaking. On the other hand, the conventional PO microporous membrane, as shown in Comparative Example 1 (Figure 2), exhibits the same stress change as that of Example 1, but the slope and magnitude of the change are significantly different.
[0026] While not wishing to be bound by theory, in the shrinkage stress mode in the MD of TMA for the PO microporous membrane, the shrinkage from around 70°C to 80°C is attributed to the relaxation of the residual stress of the membrane, and the inflection point at around 140°C is presumed to be caused by the rapid increase in shrinkage stress as the melting point is reached and pore clogging occurs. From this perspective, the shrinkage stress S at 140°C measured by the shrinkage stress mode in the MD of TMA of the present embodiment 140 and the maximum shrinkage stress S above 140°C max , the PO microporous membrane having a stress gradient A value of 0.030 or more and 0.070 or less calculated from the two points, as described above, is an ultra-high molecular weight polyethylene with Mv exceeding 1,000,000, and while ensuring highly oriented extended chains, the extended chains are sufficiently thermally fixed and / or the component amount of high molecular weight polyethylene molecular chains with strong entanglement is small, so that the residual stress is suppressed and the shrinkage stress is also low. Thus, it is considered that the membrane can be used as a separator with higher strength and lower thermal shrinkage than conventional products.
[0027] From the viewpoint of obtaining an electrochemical device that achieves a high level of both high puncture strength and low thermal shrinkage for the PO microporous membrane, ensures mechanical strength even in a thin film, and combines high energy density and high safety that guarantees dimensional retention at high temperatures, the lower limit of the aforementioned stress gradient A is preferably 0.033 or more, more preferably 0.036 or more, further preferably 0.039 or more, still more preferably 0.042 or more, particularly preferably 0.044 or more, remarkably preferably 0.046 or more, and most preferably 0.048 or more, and the upper limit of the aforementioned stress gradient A is preferably 0.068 or less, more preferably 0.066 or less, further preferably 0.064 or less, still more preferably 0.062 or less, and particularly preferably 0.060 or less.
[0028] Shrinkage stress S at 140°C measured in the shrinkage stress mode in the MD of TMA of the PO microporous membrane 140 and the maximum shrinkage stress S above 140°C max As means for controlling the value of the stress gradient A calculated from the two points within the aforementioned numerical range, for example, in the method for producing the PO microporous membrane described later, adjusting the Mv of the PE raw material described later, adjusting the raw material composition, performing atomization treatment, adjusting the stretch areal magnification and / or stretching temperature, employing simultaneous biaxial stretching, performing the stretching step before the extraction step; adjusting the total stretch magnification of the resin molded article; during the heat setting (HS) step, adjusting the HS stretching temperature and HS relaxation temperature, adjusting to satisfy HS stretching temperature < HS relaxation temperature, adjusting the HS stretch magnification, adjusting the HS relaxation magnification, and the like can be used alone or in appropriate combination.
[0029] From the viewpoint of obtaining a low thermal shrinkage PO microporous membrane that ensures the safety of electrochemical devices even in a high temperature environment, the shrinkage stress S at 100°C measured in the shrinkage stress mode in the MD of thermomechanical analysis (TMA) of the PO microporous membrane 100 and the shrinkage stress S at 120°C 120Based on these two points, the lower limit of stress gradient B is preferably -0.010 or higher, more preferably -0.005 or higher, even more preferably -0.002 or higher, even more preferably 0.000 or higher, and particularly preferably 0.001 or higher. The upper limit of stress gradient B is preferably 0.010 or lower, more preferably 0.009 or lower, even more preferably 0.008 or lower, even more preferably 0.007 or lower, and particularly preferably 0.0006 or lower.
[0030] As described above, in the shrinkage stress mode of the TMA of the PO microporous membrane of this embodiment at MD, shrinkage from around 70°C to 80°C is thought to be due to the relaxation of residual stress in the membrane, and the value of stress gradient B is presumed to be an index that reflects that stress. As means to control the value of stress gradient B within the above numerical range, for example, in the manufacturing method of the PO microporous membrane described later, the Mv of the PE raw material described later, atomization treatment, adjustment of the stretching surface ratio and / or stretching temperature, adjustment of the HS stretching temperature and HS relaxation temperature during the heat setting (HS) process, and adjustment of the HS stretching ratio and HS relaxation ratio can be used individually or in appropriate combinations.
[0031] Maximum shrinkage stress S above 140°C measured by shrinkage stress mode at MD of TMA of PO microporous membrane max From the perspective of further improving the safety of electrochemical devices in high-temperature environments, 2.0 N / mm 2 The following is preferred: 1.8 N / mm 2 The following is more preferable: 1.6 N / mm 2 The following is even more preferable: 1.4 N / mm 2 The following is even more preferable: 1.3 N / mm 2 The following is particularly preferred: Maximum contraction stress S max The lower limit is 0.1 N / mm², from the perspective of improving the adhesion between the electrode and separator during pressing in the production process of electrochemical devices. 2 The above is preferable, and 0.2 N / mm 2 The above is more preferable, 0.3 N / mm 2 The above is even more preferable, 0.4 N / mm 2 The above is even more preferable, 0.5 N / mm2 The above are particularly preferable.
[0032] Maximum shrinkage stress S above 140°C measured by shrinkage stress mode at MD of TMA of PO microporous membrane max As means of controlling the above numerical range, for example, in the method for manufacturing a PO microporous membrane described later, the Mv of the PE raw material described later, atomization treatment, adjustment of the stretching surface ratio and / or stretching temperature, adjustment of the HS stretching temperature and HS relaxation temperature during the heat setting (HS) process, adjustment of the HS stretching ratio and HS relaxation ratio can be used individually or in appropriate combinations.
[0033] From the viewpoint of reliably ensuring the high-temperature rupture resistance of the PO microporous membrane and guaranteeing the high safety of the electrochemical device, the lower limit of the rupture temperature measured by the shrinkage stress mode in MD of the TMA of the PO microporous membrane is preferably 150°C or higher, more preferably 153°C or higher, even more preferably 155°C or higher, even more preferably 157°C or higher, and particularly preferably 159°C or higher. The upper limit of the rupture temperature is preferably 240°C or lower, more preferably 230°C or lower, even more preferably 220°C or lower, even more preferably 210°C or lower, and particularly preferably 200°C or lower.
[0034] As a means of controlling the film rupture temperature measured by the shrinkage stress mode at the MD of the TMA of the PO microporous membrane to within the above numerical range, for example, in the method for manufacturing the PO microporous membrane described later, one can adjust the composition of the PE raw material described later.
[0035] <Thermal shrinkage rate> As the range of applications for electrochemical devices expands, it is considered important to control the thermal shrinkage rate of PO microporous films used as separators at high temperatures (e.g., near the melting point of PO, or near the melting point of the PO microporous film) in order to ensure device safety in high-temperature environments. PO microporous films in which PE crystals are highly oriented and the thermal shrinkage rate is within a certain range are suitable from the viewpoint of ensuring good dimensional stability in high-temperature environments.
[0036] More specifically, to improve device safety in high-temperature environments, the thermal shrinkage rate of the PO microporous film at 105°C is preferably 12.5% or less for MD and TD, more preferably 10.0% or less for MD and TD, even more preferably 8.0% or less for MD and TD, and even more preferably 6.0% or less for MD and TD. Furthermore, the direction in which the film is not constrained within the battery is not necessarily bidirectional, and from the viewpoint of preventing contact between electrodes due to thermal shrinkage of the separator, it is even more preferable that the thermal shrinkage rate of at least one direction be 5% or less, and particularly preferable that it be 3% or less. The lower limit of the thermal shrinkage rate of the PO microporous film at 105°C can be, for example, -5% or more, -2% or more, -1% or more, or 0% or more for both MD and TD.
[0037] Means for controlling the thermal shrinkage rate of the PO microporous membrane at 105°C within the above numerical range include, for example, adjusting the PE raw material Mv, and adjusting the TD stretching and / or relaxation ratio and temperature during the heat setting (HS) process of the PO microporous membrane.
[0038] <Piercing strength> Basis weight (g / m²) of PO microporous membrane 2 The puncture strength when converted to (hereinafter referred to as the basis weight equivalent puncture strength) is 70 gf / (g / m²). 2 It is preferable that the puncture strength of the PO microporous membrane is 70 gf / (g / m²). 2 When the puncture strength is 90 gf / (g / m²) or higher, the safety of electrochemical devices when subjected to impact, such as in impact tests, and the mechanical strength of thin films tend to be good. From this trend, the basis weight equivalent puncture strength of PO microporous films is 90 gf / (g / m²). 2 It is more preferable that it be 100 gf / (g / m³) or more, 2 It is even more preferable that it be 105 gf / (g / m³) or more, 2 It is even more preferable that it be 110 gf / (g / m³) or higher, 2 It is particularly preferable that the value be ) or higher. The upper limit of the puncture strength converted to basis weight should be, from the viewpoint of suppressing thermal shrinkage, for example, 154 gf / (g / m). 2) can be less than or equal to:
[0039] The puncture strength of the PO microporous membrane, which has not been converted to basis weight (hereinafter simply referred to as puncture strength), has a lower limit of preferably 200 gf or more (i.e., about 1.96 N or more), more preferably 230 gf or more, 250 gf or more, or 280 gf or more. A puncture strength of 200 gf or more is preferable from the viewpoint of ensuring safety when an electrochemical device is subjected to impact and ensuring sufficient mechanical strength even in thin films. Furthermore, the upper limit of the puncture strength of the PO microporous membrane is preferably 680 gf or less, more preferably 630 gf or less, 600 gf or less, or 550 gf or less, from the viewpoint of orientation relaxation during heating of the membrane and the membrane stretching process.
[0040] Means for controlling the basis weight equivalent puncture strength or puncture strength of a PO microporous membrane within the above numerical range include, for example, using homo-PE raw material, adjusting the PE raw material Mv, adjusting the stretching surface ratio and / or stretching temperature in the manufacturing process of the PO microporous membrane.
[0041] <film thickness> From the viewpoint of reducing the volume of the separator within the electrochemical device and improving energy density, the thickness of the PO microporous film is preferably 15 μm or less, more preferably 12 μm or less, 10 μm or less, or 8 μm or less, and even more preferably 6 μm or less, or 5 μm or less. From the viewpoint of maintaining insulation between electrodes, the thickness of the PO microporous film is preferably 1 μm or more.
[0042] Means for controlling the film thickness of the PO microporous membrane within the above numerical range include, for example, controlling the polymer content (PC) in the molten-mixed resin, and the (die) lip clearance, cast clearance, stretching ratio, HS stretching ratio, and relaxation rate in the method for manufacturing the PO microporous membrane described later.
[0043] <Air permeability> The air permeability of PO microporous membranes is determined from the perspective of ensuring membrane permeability and maintaining the output characteristics of electrochemical devices, such as 100 cm³ of air. 3The per unit is preferably 385 seconds or less, more preferably 340 seconds or less, even more preferably 300 seconds or less, even more preferably 260 seconds or less, particularly preferably 230 seconds or less, significantly preferably 200 seconds or less, and most preferably 180 seconds or less. The lower limit of air permeability is set from the viewpoint of balancing film thickness, porosity, and pore size, with respect to 100 cm² of air. 3 Preferably, the interval is 50 seconds or more, more preferably 55 seconds or more, even more preferably 70 seconds or more, or 80 seconds or more.
[0044] Air permeability (seconds / (100cm) when the film thickness of a PO microporous membrane is converted to 10 μm 3 From the viewpoint of obtaining an electrochemical device with high permeability and high input / output density, a 1000 (second / (100 cm)) is preferable. 3 • 10 μm) or less, more preferably 800 (seconds / (100 cm) 3 • 10 μm) or less, more preferably 700 (seconds / (100 cm) 3 • 10 μm) or less, more preferably 600 (seconds / (100 cm) 3 • 10 μm) or less, particularly preferably 500 (seconds / (100 cm) 3 • 10 μm) or less, preferably 450 (seconds / (100 cm) 3 • 10 μm) or less, most preferably 400 (seconds / (100 cm) 3 The minimum value for air permeability when the film thickness is converted to 10 μm is preferably 30 (seconds / (100 cm)) from the viewpoint of ensuring mechanical strength while enabling thin film construction. 3 10 μm or more, more preferably 60 seconds / (100 cm) 3 • 10 μm or more, more preferably 80 seconds / (100 cm) 3 10 μm or more, more preferably 100 (seconds / (100 cm)) 3 • 10 μm or more, particularly preferably 120 seconds / (100 cm) 3 (10 μm) or more, preferably 140 (seconds / (100 cm) 3 • 10 μm or more, most preferably 150 (seconds / (100 cm) 3 It is 10 μm or larger.
[0045] The air permeability of the PO microporous membrane and the air permeability when the film thickness is converted to 10 μm can be controlled within the above numerical range by adjusting, for example, the HS stretching ratio, HS relaxation ratio, HS relaxation temperature, etc., in the manufacturing method of the PO microporous membrane described later.
[0046] <Porosity> The porosity of the PO microporous membrane is preferably 20% or more, more preferably 22% or more, and even more preferably 24% or more or 26% or more. A porosity of 20% or more is preferable from the viewpoint of ensuring good output characteristics. The upper limit of the porosity is preferably 50% or less, more preferably 45% or less, and even more preferably 40% or less. A porosity of 50% or less is preferable from the viewpoint of ensuring the puncture strength and dielectric strength described above. The porosity of the PO microporous membrane can be controlled within the above numerical range by, for example, adjusting the Mv of the PE raw material, performing atomization treatment, adjusting the HS stretching ratio, HS relaxation ratio, HS relaxation temperature, etc., in the method for manufacturing the PO microporous membrane described later.
[0047] <Tensile breaking strength> The tensile breaking strength of the PO microporous membrane is preferably 1500 kgf / cm² in both the MD and TD directions (MD tensile breaking strength and TD tensile breaking strength), respectively. 2 The above is preferable, and a more preferable value is 1750 kgf / cm². 2 The above is preferable, and more preferably 2000 kgf / cm². 2 More preferably, 2200 kgf / cm² 2 That concludes the explanation. The tensile breaking strength is 1500 kgf / cm². 2 As a result, rupture during slitting or winding of electrochemical devices is more suppressed, or short circuits due to foreign matter in the electrochemical device tend to be more suppressed. On the other hand, the tensile breaking strength of the PO microporous membrane is preferably 5000 kgf / cm for both MD and TD. 2 The following, and more preferably 4500 kgf / cm² 2 The following, and more preferably 4000 kgf / cm²2 or less. The tensile breaking strength of the PO microporous film is 5000 kgf / cm 2 or less, so that the PO microporous film relaxes early during a heating test to reduce the shrinkage force, and as a result, the safety tends to be improved.
[0048] The ratio of the MD tensile breaking strength to the TD tensile breaking strength (MD strength / TD strength) of the PO microporous film is preferably 0.3 or more and 3.0 or less, more preferably 0.4 or more and 2.5 or less, and even more preferably 0.5 or more and 2.0 or less, from the viewpoint of ensuring the productivity and yield of electrochemical devices resulting from the resistance of the separator to tearing.
[0049] <Components Contained in PO Microporous Film> The PO microporous film according to the present embodiment is formed from a resin composition containing a polyolefin resin, and contains polyethylene (PE) as a main component. If desired, the resin composition may further contain inorganic particles, resins other than polyolefins, and the like. The total content (PC) of all resins contained in the PO resin composition is preferably 34 mass% or less from the viewpoints of the strength and film thickness of the PO microporous film.
[0050] The polyolefin resin used in the present embodiment is not particularly limited except that it contains polyethylene as a main component, and examples thereof include polymers obtained by polymerizing monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene (for example, homopolymers, copolymers, multistage polymers, and the like). These polymers may be used alone or in combination of two or more.
[0051] The total proportion of the PE raw material in the PO raw material is preferably 50 mass% to 100 mass%, and more preferably 80 mass% to 100 mass%, from the viewpoint of developing shutdown characteristics.
[0052] The PO microporous membrane preferably contains 55% by mass or more, more preferably 65% by mass or more, and even more preferably 75% by mass or more, of polyethylene (PE) raw material with an Mv of 1,000,000 to 9,000,000, based on the mass of the PO microporous membrane. When the PO microporous membrane contains 55% by mass or more of PE raw material with an Mv of 1,000,000 to 9,000,000, the crystals become highly oriented during stretching, which tends to result in a PO microporous membrane with high strength and low thermal shrinkage. From a similar viewpoint, the PO raw material used in the production of the PO microporous membrane is preferably an ethylene homopolymer, and more preferably an ethylene homopolymer with an Mv of 1,000,000 to 9,000,000. The amount of polyolefin resin contained in the PO microporous membrane is preferably 60% by mass or more, preferably 70% by mass or more, preferably 80% by mass or more, and may be 90% by mass or more, based on the mass of the PO microporous membrane.
[0053] Furthermore, as a polyolefin resin, for example, low-density polyethylene (density 0.910 g / cm³) is used. 3 More than 0.930g / cm 3 (less than), linear low-density polyethylene (density 0.910 g / cm³) 3 More than 0.940g / cm 3 (less than), medium-density polyethylene (density 0.930 g / cm³) 3 More than 0.942g / cm 3 (less than), high-density polyethylene (density 0.942 g / cm³) 3 (The above) Ultra-high molecular weight polyethylene (density 0.910 g / cm³) 3 More than 0.970g / cm 3 Examples include polyethylene (less than 350 lb), isotactic polypropylene, atactic polypropylene, polybutene, ethylene propylene rubber, etc. These can be used individually or in combination of two or more. In particular, using only polyethylene, only polypropylene, or a mixture of polyethylene and polypropylene is preferable from the viewpoint of obtaining a uniform film.
[0054] Furthermore, from the perspective of safety in electrochemical devices that utilize a PO microporous membrane as a separator, polyolefin resin is suitable at 0.930 g / cm³. 3 More than 0.942g / cm 3 It is preferable that the PO microporous membrane is a medium-density polyethylene (PE) having a density of less than 1 million, for example, any PE other than high-density polyethylene (HDPE) is acceptable. Furthermore, from the viewpoint of improving the safety of electrochemical devices even when the PO microporous membrane is a thin film, medium-density polyethylene with a viscosity-average molecular weight of less than 1 million, and polyethylene with a viscosity-average molecular weight of 1 million to 2 million and a density of 0.930 g / cm³ are preferred. 3 More than 0.942g / cm 3 It is preferable that at least one type selected from ultra-high molecular weight polyethylene of less than 50% by mass be included, more preferably 60% by mass or more, and most preferably 70% by mass or more, based on the mass of the PO microporous membrane.
[0055] From the viewpoint of ensuring safety in high-temperature ranges (above 160°C) where safety is difficult to ensure with PE, polyolefin resins preferably contain polypropylene (PP). As for polypropylene, propylene homopolymer is preferred from the viewpoint of heat resistance. From the viewpoint of further improving heat resistance, it is more preferable for the polyolefin resin to contain both polyethylene as a main component and polypropylene. Therefore, the proportion of PP raw material in the PO raw material is preferably greater than 0% by mass and 10% by mass or less. Here, including a specific component as a main component means that the content of that specific component is 50% by mass or more.
[0056] When using PE and PP together, the polyethylene should be medium-density polyethylene with a viscosity-average molecular weight of less than 1 million, or polyethylene with a viscosity-average molecular weight of 1 million to 9 million and a density of 0.930 g / cm³. 3 More than 0.942g / cm 3Using at least one type of ultra-high molecular weight polyethylene with a viscosity-average molecular weight of less than 9 million is preferable from the viewpoint of balancing strength and permeability and maintaining an appropriate shutdown temperature. Furthermore, it is even more preferable from the viewpoint of maintaining an appropriate shutdown temperature to not include ultra-high molecular weight polyethylene with a viscosity-average molecular weight of 9 million or more.
[0057] The viscosity-average molecular weight of the PO resin (measured according to the measurement method described in the examples below) is preferably 500,000 to 9,000,000. A higher molecular weight of the PO resin itself makes it easier to achieve film strength, and tends to improve safety in various device safety tests such as impact tests and oven tests. From this viewpoint, the Mv of the PO resin is more preferably 1,000,000 or higher, even more preferably 1,500,000 or higher, even more preferably 2,000,000 or higher, particularly preferably 2,500,000 or higher, and most preferably 3,000,000 or higher. On the other hand, adjusting the viscosity-average molecular weight of the PO resin to 9,000,000 or lower is preferable from the viewpoint of suppressing thermal shrinkage during the HS process.
[0058] The value obtained by dividing the weight-average molecular weight (Mw) of the polyethylene raw material by the number-average molecular weight (Mn) (Mw / Mn) is preferably between 4.0 and 12.0. From the viewpoint of balancing high strength, high permeability, and low heat shrinkage of the PO microporous membrane, the lower limit of the Mw / Mn of the polyethylene raw material is preferably 6.0 or higher, and more preferably 7.0 or higher. Furthermore, from the viewpoint of the decrease in porosity during HS, the upper limit is preferably 12.0 or lower, and more preferably 10.0 or lower. Therefore, the preferred range for the Mw / Mn of the polyethylene raw material is, in order: 6.0 to 12.0, 7.0 to 12.0, 4.0 to 10.0, 6.0 to 10.0, and 7.0 to 10.0. The weight-average molecular weight (Mw), number-average molecular weight (Mn), and Mw / Mn of the polyethylene raw material are the polyethylene-convertible molecular weight obtained by GPC (gel permeation chromatography) measurement.
[0059] The resin composition may optionally contain inorganic particles, antioxidants such as phenolic, phosphorus-based, or sulfur-based compounds; metal soaps such as calcium stearate or zinc stearate; and various known additives such as ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, and coloring pigments.
[0060] [Method for manufacturing polyolefin microporous membranes] The PO microporous membrane according to this embodiment may be manufactured by any method known in the art, as long as it has the properties described above. While not particularly limited, for example, a polyolefin membrane may be formed by melt extrusion of a polyolefin resin, followed by stretching, and its porosity can be created by a wet process. Wet methods include, for example, adding a pore-forming agent such as a plasticizer to polyolefin, dispersing it, molding it, then extracting the pore-forming agent with a solvent to form pores, and performing stretching before and after extraction as needed.
[0061] One example of a manufacturing method is a mixing step (a) in which a resin composition containing polyolefin resin and various additives as desired is mixed, The mixture obtained in step (a) is melted and kneaded and then extruded in extrusion step (b), The sheet forming process (c) involves forming the extruded material obtained in process (b) into a sheet, The sheet-like molded product obtained in step (c) is stretched at least once in at least one axial direction in a primary stretching step (d), The extraction step (e) involves extracting pore-forming material from the primary stretched film obtained in step (d), A method is provided which includes a heat-fixing step (f) in which the extracted film obtained in step (e) is heat-fixed (HS) at a predetermined temperature.
[0062] The above method for manufacturing a PO microporous membrane provides a PO microporous membrane that exhibits high puncture strength, high permeability, and low thermal shrinkage when used as a separator for lithium-ion secondary batteries and other electrochemical devices. In particular, the method in which polyolefin resin is micronized in a mixing step (a) either alone or in a mixture with a liquid plasticizer such as liquid paraffin, then stretched to MD and TD in a primary stretching step (d), and then heat-fixed to TD in a heat-fixing step (f) after an extraction step (e) tends to make it easier to adjust the strength, pore size, and thermal shrinkage rate of the resulting PO microporous membrane within the numerical range described above. It should be noted that the method for manufacturing a PO microporous membrane in this embodiment is not limited to the above method, and various modifications are possible without departing from its essence.
[0063] [Mixing step (a)] Mixing step (a) is a step of mixing a resin composition containing a polyolefin resin and various additives as desired. In addition, other components may be mixed with the resin composition in mixing step (a) as needed.
[0064] The pore-forming material can be any material as long as it is distinguishable from the PO resin and inorganic particle material, and can be, for example, a plasticizer. As the plasticizer, a non-volatile solvent that can form a homogeneous solution above the melting point of the PO resin may be used, such as hydrocarbons such as liquid paraffin (LP) and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; or higher alcohols such as oleyl alcohol and stearyl alcohol.
[0065] The plasticizer content in the resin composition is preferably 60% to 90% by mass, more preferably 65% to 85% by mass, and even more preferably 70% to 80% by mass. Adjusting the plasticizer content to 60% or more by mass tends to lower the melt viscosity of the resin composition and suppress melt fracture, thereby improving film-forming properties during extrusion. On the other hand, adjusting the plasticizer content to 90% by mass or less can suppress the elongation of the raw material during the film-forming process.
[0066] (Optional additives) In step (a), the resin composition containing PO may contain any additives. The additives are not particularly limited, but examples include polymers other than polyolefin resins; antioxidants such as phenolic compounds, phosphorus compounds, and sulfur compounds; metal soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; and coloring pigments. The total amount of these additives added is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the polyolefin resin.
[0067] The mixing method in step (a) is not particularly limited, but for example, some of the raw materials may be pre-mixed using a Henschel mixer, ribbon blender, tumbler blender, etc., as needed. Among these, the method of mixing using a Henschel mixer is preferred.
[0068] Furthermore, in step (a) above, it is preferable to include a process of atomizing a part or all of the polyolefin resin, either alone or, if desired, in a mixture with the various additives and / or other components. If the polyolefin resin contains ultra-high molecular weight polyethylene, it is even more preferable to include a process of atomizing a part or all of the ultra-high molecular weight polyethylene in a mixture with a liquid plasticizer such as liquid paraffin, from the viewpoint of ensuring moldability in step (b) and beyond.
[0069] While we do not wish to be bound by theory, it has been found that the atomization process described herein reduces the proportion of relatively high molecular weights and increases the proportion of relatively low molecular weights in the molecular weight distribution of the atomized resin raw material. This can achieve, for example, an increase in the swelling rate of the resin raw material in the presence of pore-forming material, uniformity of film properties due to stabilization in the extrusion process, a reduction or elimination of relatively small pores and retention of relatively large pores in the pore size distribution, improvement of the stretchability of sheet-like molded products and films after extraction of pore-forming material, and improvement of the shrinkage stress of microporous films, and indirectly, an improvement in film strength. Furthermore, if a polyolefin microporous film obtained by a manufacturing method including the atomization process is used as a separator for electrochemical devices, even thin-film separators can be made mechanically strong, resulting in high energy density, and achieving a high degree of compatibility between high input / output density and high safety with excellent dimensional stability at high temperatures.
[0070] Methods for atomization are not particularly limited, but include processes that apply atomizing force by applying physical impact force, shear force, compressive force, vibration force, cavitation force, etc., either individually or in combination. Specifically, examples include using pulverizers such as ball mills, bead mills, ring mills, jet mills, rod mills, and roll mills, or homogenizers and homomixers of the high-pressure, ultrasonic, or ultra-high-speed type, either individually or in combination. Among these, the method using a beer mill or homogenizer is preferred, and the use of a high-pressure method is more preferred.
[0071] [Extrusion process (b)] Extrusion step (b) is a step in which the resin composition obtained in step (a) is melted, kneaded, and extruded. In addition, other components may be mixed with the resin composition in extrusion step (b) as needed.
[0072] The method of melt-kneading in step (b) is not particularly limited, but for example, all raw materials, including the mixture mixed in step (a), can be melt-kneaded using a screw extruder such as a single-screw extruder or twin-screw extruder; a kneader; a mixer, etc. Among these, it is preferable to perform the melt-kneading using a screw with a twin-screw extruder. Furthermore, when performing melt-kneading, it is preferable to add the plasticizer in two or more stages, and when adding the additive in multiple stages, it is preferable to adjust the amount added in the first stage so that it is 80% by weight or less of the total amount added, from the viewpoint of suppressing aggregation of contained components and dispersing them uniformly. This is preferable from the viewpoint of suppressing heat generation by shutting down a large area and improving the safety of the cell.
[0073] When a pore-forming agent is used in step (b), the temperature of the melt-mixing section is preferably less than 200°C from the viewpoint of uniformly mixing the resin composition. The lower limit of the temperature in the melt-mixing section is above the melting point of the polyolefin from the viewpoint of uniformly dissolving the polyolefin resin into the plasticizer.
[0074] In this embodiment, during the kneading process, although not particularly limited, it is preferable to first mix an antioxidant with the raw material PO at a predetermined concentration, then replace the surrounding atmosphere of the mixture with a nitrogen atmosphere, and perform melt kneading while maintaining the nitrogen atmosphere.
[0075] In step (b), the kneaded material obtained after the kneading process is extruded by an extruder such as a T-die or annular die. At this time, it may be single-layer extrusion or laminated extrusion. The conditions during extrusion are not particularly limited, and known methods can be used, for example. Furthermore, from the viewpoint of the thickness of the resulting PO microporous film, it is preferable to control the (die) lip clearance and the like.
[0076] [Sheet forming process (c)] The sheet forming process (c) is a process of forming the extruded material obtained in the extrusion process (b) into a sheet. The sheet-like molded material obtained in the sheet forming process (c) may be a single layer or a laminate. The method of sheet forming is not particularly limited, but one example is a method of solidifying the extruded material by compression and cooling.
[0077] The compression cooling method is not particularly limited, but examples include a method of directly contacting the extruded material with a cooling medium such as cold air or cooling water; or a method of contacting the extruded material with a metal roll or press machine cooled with a refrigerant. Among these, the method of contacting the extruded material with a metal roll or press machine cooled with a refrigerant is preferred because it allows for easy control of the film thickness.
[0078] In the process of forming the molten material into a sheet after the melt-kneading step (b), it is preferable to set the temperature higher than the set temperature of the extruder. From the viewpoint of thermal degradation of the polyolefin resin, the upper limit of the set temperature is preferably 300°C or less, and more preferably 260°C or less. For example, when continuously producing sheet-shaped molded articles from an extruder, it is preferable that the set temperature of the process of forming the molten material into a sheet after the melt-kneading step, i.e., the path from the extruder outlet to the T-die, and the T-die, are set higher than the set temperature of the extrusion step, because it is possible to form the molten material into a sheet without separation of the resin composition and the pore-forming material. Furthermore, from the viewpoint of the film thickness of the resulting PO microporous film, it is preferable to control the cast clearance and the like.
[0079] The thickness of the resulting sheet-like molded article can be between 600 μm and 2000 μm, depending on, for example, the thickness after stretching in step (d).
[0080] [Primary stretching process (d)] The primary stretching step (d) is a step in which the sheet-like molded product obtained in the sheet forming step (c) is stretched at least once in at least one axial direction. This stretching step (a stretching step performed before the next extraction step (e)) will be called "primary stretching," and the film obtained by primary stretching will be called "primary stretched film." In primary stretching, the sheet-like molded product can be stretched in at least one direction, and may be performed in both MD and TD directions, or in only one of MD or TD directions.
[0081] The primary stretching method is not particularly limited, but examples include uniaxial stretching using a roll stretcher; TD uniaxial stretching using a tenter; sequential biaxial stretching using a roll stretcher and a tenter, or a combination of multiple tenters; and simultaneous biaxial stretching using a simultaneous biaxial tenter or inflation molding. Among these, simultaneous biaxial stretching is preferred from the viewpoint of improving safety when the electrochemical device is subjected to impact, such as in impact tests, and the physical stability of the resulting PO microporous film.
[0082] The stretching ratio of the MD and / or TD in the primary stretching is preferably 5 times or more, more preferably 6 times or more. A stretching ratio of 5 times or more in the MD and / or TD in the primary stretching tends to further improve the strength of the resulting PO microporous film. Alternatively, the stretching ratio of the MD and / or TD in the primary stretching is preferably 9 times or less, more preferably 8 times or less, or 7 times or less. A stretching ratio of 9 times or less in the MD and / or TD in the primary stretching tends to further suppress breakage during stretching. When performing biaxial stretching, either sequential stretching or simultaneous biaxial stretching may be used, but the stretching ratio in each axial direction is preferably 5 times or more and 9 times or less, more preferably 6 times or more and 8 times or less, or 6 times or more and 7 times or less.
[0083] The primary stretching temperature can be selected by referring to the raw material resin composition and concentration contained in the PO resin composition. The stretching temperature for MD and / or TD is preferably in the range of 100°C to 135°C, more preferably 110°C to 130°C, even more preferably 115°C to 128°C, and even more preferably in the range of 116°C to 122°C, 118°C to 122°C, or 116°C to 118°C. For both MD and TD, the stretching temperature is preferably 100°C or higher from the viewpoint of suppressing breakage, and preferably 135°C or lower from the viewpoint of increasing film strength.
[0084] [Extraction step (e)] The extraction step (e) is a step of extracting pore-forming material from the primary stretched film obtained in the primary stretching step (d) to obtain an extracted film. Methods for removing the pore-forming material include, for example, immersing the primary stretched film in an extraction solvent to extract the pore-forming material and then drying it thoroughly. The method for extracting the pore-forming material may be either batch or continuous. Furthermore, it is preferable that the residual amount of pore-forming material, particularly plasticizer, in the porous film be less than 1% by mass.
[0085] When extracting pore-forming materials, it is preferable to use an extraction solvent that is a poor solvent for polyolefin resins and a good solvent for pore-forming materials or plasticizers, and whose boiling point is lower than the melting point of the polyolefin resin. Such extraction solvents are not particularly limited, but examples include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as methylene chloride and 1,1,1-trichloroethane; non-chlorinated halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. These extraction solvents may be recovered and reused by operations such as distillation.
[0086] [Heat setting process (f)] The heat-fixing step (f) is a step in which the extracted film obtained in the extraction step (e) is heat-fixed at a predetermined temperature. The method of heat treatment in this step is not particularly limited, but one example is a heat-fixing method that involves stretching and relaxing operations using a tenter or roll stretcher.
[0087] The stretching operation in the heat-setting step (f) is an operation in which the PO microporous film is stretched in at least one direction of MD and TD, and may be performed in both directions of MD and TD, or in only one of MD or TD. From the viewpoint of obtaining a PO microporous film with high strength and high permeability, it is preferable to perform heat-setting in at least the TD direction.
[0088] The stretching ratios of MD and TD in the heat-setting process (f) are preferably 1.50 times or more and 2.20 times or less, and more preferably 1.80 times or more and 2.10 times or less. From the viewpoint of highly oriented the film and developing film strength, the stretching ratios of MD and TD in process (f) are preferably 1.50 times or more, and from the viewpoint of suppressing breakage, they are preferably 2.20 times or less.
[0089] From the viewpoint of the melting point of the polyolefin resin, the MD and / or TD stretching temperature during heat setting is preferably 100°C to 170°C. From the viewpoint of controlling the pore size to obtain a PO microporous film with a balanced combination of high puncture strength, high permeability, and low thermal shrinkage, the lower limit of the stretching temperature during heat setting is more preferably 110°C or higher, even more preferably 120°C or higher, even more preferably 125°C or higher, and particularly preferably 129°C or higher, and the upper limit of the stretching temperature during heat setting is more preferably 160°C or lower, even more preferably 150°C or lower, even more preferably 140°C or lower, and particularly preferably 138°C or lower.
[0090] The relaxation operation in the heat-setting process (f) is an operation to shrink the PO microporous film in at least one of the MD and TD directions, and may be performed in both directions, or in only one of the MD or TD directions. The relaxation ratio in the heat-setting process (f) is preferably 0.95 times or less, more preferably 0.90 times or less, and even more preferably 0.85 times or less. A relaxation ratio of 0.95 or less in process (f) tends to suppress thermal shrinkage. Furthermore, from the viewpoint of increasing the relaxation temperature, the relaxation ratio is preferably 0.50 times or more, and more preferably 0.70 or more. Here, "relaxation ratio" refers to the value obtained by dividing the dimensions of the film after the relaxation operation by the dimensions of the film before the relaxation operation, and if both MD and TD are relaxed, it is the value obtained by multiplying the relaxation ratio of MD by the relaxation ratio of TD. Relaxation ratio = (Dimensions of the membrane after relaxation (m)) / (Dimensions of the membrane before relaxation (m))
[0091] From the viewpoint of the pore size of the resulting PO microporous film, the relaxation temperature in this relaxation operation is preferably higher than the stretching temperature in the heat-fixing step (f). This not only removes residual stress from the stretching step, resulting in a PO microporous film with low thermal shrinkage, but also allows for control of the pore size to achieve high strength and high permeability, as well as firmly fixing the orientation of the molecular chains. Therefore, from the viewpoint of preventing a decrease in ion permeability near the melting point of the PO microporous film and improving the performance of electrochemical devices, the lower limit of the relaxation temperature during heat-fixing is preferably 100°C or higher, more preferably 110°C or higher, even more preferably 120°C or higher, even more preferably 125°C or higher, and particularly preferably 129°C or higher. The upper limit of the relaxation temperature during heat-fixing is preferably 170°C or lower, more preferably 160°C or lower, even more preferably 150°C or lower, even more preferably 140°C or lower, and particularly preferably 138°C or lower.
[0092] The order of steps (a) to (f) above can be changed as desired, as long as it does not impair the effects of the present invention. After steps (a) to (f) above, the total stretching ratio of the PO microporous film is preferably in the range of 50 to 100 times, more preferably in the range of 60 to 90 times, and even more preferably in the range of 70 to 80 times. Here, "total stretching ratio" refers to the value obtained by multiplying the stretching ratio of MD and / or TD in the primary stretching step (d) by the stretching ratio and / or relaxation ratio in the heat setting step.
[0093] [Other processes] The method for manufacturing a PO microporous film according to this embodiment may include other steps besides the above steps (a) to (f). These other steps are not particularly limited, but for example, in addition to the heat-setting step, a lamination step may be used to obtain a laminated PO microporous film by stacking multiple single-layer PO microporous films. Alternatively, the method for manufacturing a PO microporous film may include a peeling step to obtain two or more single layers by peeling off the laminate obtained by co-extrusion after steps (a) to (f). Furthermore, the method for manufacturing a PO microporous film according to this embodiment may include a surface treatment step in which the surface of the PO microporous film is subjected to surface treatment such as electron beam irradiation, plasma irradiation, surfactant application, or chemical modification. Moreover, an inorganic particle material may be coated onto one or both sides of the PO microporous film to obtain a PO microporous film equipped with an inorganic material layer.
[0094] <Formation of inorganic coating layer> From the viewpoints of safety, dimensional stability, and heat resistance, an inorganic coating layer can be provided on the surface of the PO microporous film. The inorganic coating layer is a layer containing inorganic components such as inorganic particles, and may optionally contain a binder resin to bind the inorganic particles together, a dispersant to disperse the inorganic particles in a solvent, and so on.
[0095] Examples of materials for inorganic particles contained in the inorganic coating layer include oxide ceramics such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, barium sulfate, aluminum hydroxide, aluminum hydroxide oxide, potassium titanate, talc, kaolinite, decite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amethyst, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. Inorganic particles may be used individually or in combination. Examples of binder resins include conjugated diene polymers, acrylic polymers, polyvinyl alcohol-based resins, and fluoropolymer resins. The binder resin can also be in the form of latex and may contain water or an aqueous solvent. Dispersants are substances that adsorb to the surface of inorganic particles in a slurry and stabilize the inorganic particles through electrostatic repulsion, etc. Examples include polycarboxylates, sulfonates, polyoxyethers, and surfactants.
[0096] In the particle size distribution of inorganic particles, the particle size D50 is preferably in the range of 0.05 μm to 1.2 μm, more preferably 0.05 μm to 0.8 μm, and even more preferably 0.05 μm to 0.5 μm. When D50 is 0.05 μm or larger, migration of inorganic particles from the porous layer into the pores of the PO microporous membrane is suppressed, which can improve the permeability of the multilayer porous membrane. Furthermore, when D50 is 1.2 μm or smaller, heat resistance of the porous layer is more easily obtained.
[0097] The inorganic coating layer can be formed, for example, by applying and drying a slurry of the components described above onto the surface of a PO microporous film.
[0098] <Formation of the adhesive layer> To prevent deformation or bulging due to gas generation in laminate-type batteries, which have recently been increasingly adopted for automotive batteries to increase energy density, an adhesive layer containing a thermoplastic resin can be provided on the surface of the PO microporous membrane. The thermoplastic resin contained in the adhesive layer is not particularly limited and includes, for example, polyolefins such as polyethylene or polypropylene; fluororesins such as polyvinylidene fluoride and polytetrafluoroethylene; fluororubbers such as vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer; styrene-butadiene copolymer and its hydride, acrylonitrile-butadiene copolymer and its hydride, acrylonitrile-butadiene-styrene Examples include rubbers such as styrene copolymers and their hydrogenates, (meth)acrylic acid ester copolymers, styrene-acrylic acid ester copolymers, acrylonitrile-acrylic acid ester copolymers, ethylene propylene rubber, polyvinyl alcohol, and polyvinyl acetate; cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; and resins with a melting point and / or glass transition temperature of 180°C or higher, such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester.
[0099] Furthermore, after the heat setting process (f), the lamination process, or the surface treatment process, the master roll on which the PO microporous film is wound can be subjected to an aging process under predetermined temperature conditions before the rewinding operation of the master roll. This tends to make it easier to obtain a PO microporous film with higher thermal stability than the PO microporous film before rewinding. In the above case, the temperature during the aging process of the master roll is not particularly limited, but is preferably 35°C or higher, more preferably 45°C or higher, and even more preferably 60°C or higher. Also, from the viewpoint of maintaining the permeability of the PO microporous film, the temperature during the aging process of the master roll is preferably 120°C or lower. The time required for the aging process is not particularly limited, but is preferably 24 hours or more because the above effects are more likely to occur.
[0100] <Separators for electrochemical devices> The polyolefin microporous membrane according to this embodiment can be used as a separator for electrochemical devices such as lithium-ion secondary batteries. By incorporating the polyolefin microporous membrane into a lithium-ion secondary battery, thermal runaway of the lithium-ion secondary battery can be suppressed.
[0101] <Electrochemical Devices> An electrochemical device containing a wound or laminated body formed by winding or stacking multiple PO microporous membranes according to this embodiment is also an embodiment of the present invention. Examples of electrochemical devices include non-aqueous electrolyte batteries, non-aqueous lithium-ion secondary batteries, non-aqueous gel secondary batteries, non-aqueous solid secondary batteries, lithium-ion capacitors, electric double-layer capacitors, and the like.
[0102] The non-aqueous electrolyte battery according to this embodiment comprises a separator for non-aqueous electrolyte batteries containing the above-described PO microporous membrane, a positive electrode plate, a negative electrode plate, and a non-aqueous electrolyte (containing a non-aqueous solvent and a metal salt dissolved therein). Specifically, for example, a positive electrode plate containing a transition metal oxide capable of intercepting and releasing lithium ions, and a negative electrode plate capable of intercepting and releasing lithium ions are wound or stacked facing each other via a separator for non-aqueous electrolyte batteries, and the non-aqueous electrolyte is contained within the container.
[0103] The positive electrode plate is described below. As the positive electrode active material, for example, lithium composite metal oxides such as lithium nickelate, lithium manganeseate, or lithium cobaltate, or lithium composite metal phosphates such as lithium iron phosphate can be used. The positive electrode active material is kneaded with a conductive agent and a binder, and the positive electrode paste is applied to a positive electrode current collector such as aluminum foil and dried, then rolled to a predetermined thickness and cut to a predetermined size to form a positive electrode plate. Here, as the conductive agent, a metal powder that is stable under positive electrode potential, for example, carbon black such as acetylene black or graphite material can be used. As the binder, a material that is stable under positive electrode potential, for example, polyvinylidene fluoride, modified acrylic rubber, or polytetrafluoroethylene can be used.
[0104] The negative electrode plate is described below. As the negative electrode active material, a material capable of intercalating lithium can be used. Specifically, for example, at least one material selected from the group consisting of graphite, silicide, and titanium alloy materials can be used. Furthermore, as the negative electrode active material for a non-aqueous electrolyte secondary battery, for example, metals, metal fibers, carbon materials, oxides, nitrides, silicon compounds, tin compounds, or various alloy materials can be used. In particular, silicon (Si) or tin (Sn) elements or alloys, compounds, solid solutions, or other silicon or tin compounds are preferred because they tend to increase the capacity density of the battery.
[0105] Examples of carbon materials include various types of natural graphite, coke, carbon in the process of graphitization, carbon fibers, spheroidal carbon, various types of artificial graphite, and amorphous carbon.
[0106] As the negative electrode active material, one of the above materials may be used alone, or two or more may be used in combination. The negative electrode active material is kneaded with a binder, and the negative electrode paste is applied to a negative electrode current collector such as copper foil and dried, then rolled to a predetermined thickness and cut to a predetermined size to form a negative electrode plate. Here, as the binder, a material that is stable under negative electrode potential, such as PVDF or styrene-butadiene rubber copolymer, can be used.
[0107] Non-aqueous electrolytes are described below. Non-aqueous electrolytes generally contain a non-aqueous solvent and metal salts such as lithium salts, sodium salts, and calcium salts dissolved therein. Examples of non-aqueous solvents include cyclic carbonate esters, linear carbonate esters, and cyclic carboxylic acid esters. Examples of lithium salts include LiPF6, LiClO4, LiBF4, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, Li(CF3SO2)2, LiAsF6, lithium lower aliphatic carboxylates, LiCl, LiBr, LiI, borates, and imide salts.
[0108] Unless otherwise specified, the various parameters mentioned above are measured in accordance with the measurement methods described in the examples below. [Examples]
[0109] Next, this embodiment will be described in more detail with reference to examples and comparative examples, but this embodiment is not limited to the following examples unless it exceeds the gist of the embodiment. The physical properties in the examples were measured by the following methods. Unless otherwise specified, measurements were taken in an environment of 23°C and 40% humidity.
[0110] (1) Molecular weight and density (1a) Viscosity average molecular weight (Mv) Based on ASTM-D4020, the intrinsic viscosity [η] (dl / g) at 135°C in decalin solvent was determined. For PO microporous membranes and polyethylene raw materials, Mv was calculated using the following formula. [η] = 6.77 × 10-4 Mv 0.67 For polypropylene raw materials, Mv was calculated using the following formula. [η] = 1.10 × 10 -4 Mv 0.80
[0111] (1b) Weight-average molecular weight (Mw) and molecular weight distribution • Sample preparation 0.5 g of polyolefin raw material or PO microporous membrane was weighed, 20 mL of o-dichlorobenzene (with BHT added) was added, and the mixture was shaken at 145°C to dissolve it. This eluent was filtered through a 1.0 μm filter, and the filtrate was used as the GPC measurement sample. GPC measurement Using the GPC measurement samples prepared as described above, GPC measurements were performed under the following conditions. • Equipment: Polymer Char GPC-IR high-temperature gel permeation chromatograph • Detector: IR6 type MCT infrared detector • Columns: Two each of TSKgel GMH6-HT and GMH6-HTL manufactured by Tosoh Corporation. Column temperature: 140℃ ·Flow rate: 0.4mL / min Furthermore, a calibration curve was created using commercially available monodisperse polystyrene with a known molecular weight as a standard substance, and molecular weight distribution data in polystyrene equivalent was obtained for each sample. In the case of polyethylene, the molecular weight distribution data in polyethylene equivalent was obtained by multiplying the polystyrene equivalent molecular weight distribution data by 0.43 (polyethylene Q factor / polystyrene Q factor = 17.7 / 41.3). From this, the weight-average molecular weight (Mw) of each sample was obtained. In addition, from the molecular weight distribution curve with the horizontal axis representing the log molecular weight in polyethylene equivalent and the vertical axis representing the integral of mass%, the ratio of components with a molecular weight of 300,000 or less and the ratio of components with a molecular weight of 3,000,000 or more to the total molecular weight components were calculated.
[0112] (1c) Density (g / cm 3 ) The density of the sample was measured using the density gradient tube method (23°C) in accordance with JIS K7112:1999.
[0113] (2) Film thickness (μm) The film thickness of PO microporous films or porous layers was measured at room temperature (23±2°C) using a microthickness gauge, KBM (trademark), manufactured by Toyo Seiki Co., Ltd.
[0114] (3) Porosity (%) A 10cm x 10cm square sample is cut from a PO microporous membrane, and its volume (cm³) is measured. 3 Calculate the mass (g) and density (g / cm³), and then compare them with the density (g / cm³). 3 The porosity was calculated using the following formula. Porosity (%) = (Volume - Mass / Density) / Volume × 100
[0115] (4) Air permeability (sec / 100cm 3 ) The air permeability was defined as the air resistance in accordance with JIS P-8117. The air permeability of the PO microporous membrane was measured in accordance with JIS P-8117, using a Gurley-type air permeability meter, G-B2 (trademark), manufactured by Toyo Seiki Co., Ltd., under conditions of 23°C and 40% humidity. The air permeability was determined by measuring the air resistance of the PO microporous membrane. Air permeability (seconds / 100cm) 3 Dividing this by the thickness of the PO microporous membrane (μm) and multiplying by 10 μm gives the air permeability (seconds / (100 cm) when the thickness of the PO microporous membrane is converted to 10 μm. 3 We calculated the thickness of 10 μm.
[0116] (5) Puncture strength (gf) and area weight conversion puncture strength (gf / (g / m 2 )) A needle with a hemispherical tip having a radius of 0.5 mm was prepared, a PO microporous membrane was sandwiched between two plates each having an opening with a diameter (dia.) of 11 mm, and the needle, the PO microporous membrane and the plates were set. Using "MX2-50N" manufactured by Imada Co., Ltd., a puncture test was performed under the conditions of a needle tip curvature radius of 0.5 mm, an opening diameter of the PO microporous membrane holding plate of 11 mm, and a puncture speed of 25 mm / min. The needle was brought into contact with the PO microporous membrane, and the maximum puncture load (i.e., puncture strength (gf)) was measured. If desired, by dividing the puncture strength (gf) by the thickness (μm) of the PO microporous membrane and multiplying the result by 10 μm, the puncture strength (gf / 10 μm) when the thickness of the PO microporous membrane is converted to 10 μm can also be determined. In addition, the puncture strength in terms of basis weight (gf / (g / m 2 )) was also calculated.
[0117] (6) MD tensile breaking strength (kgf / cm 2 ) and TD tensile breaking strength (kgf / cm 2 ) The tensile breaking strength of the PO microporous membrane was measured using a tensile tester (TG-1 kN model manufactured by Minebea Co., Ltd.) by setting the sample length before the test to 35 mm and pulling the sample at a speed of 100 mm / min. The value obtained by dividing the strength (tensile load value) when the sample was cut (broken) by the cross-sectional area of the test piece was defined as the tensile breaking strength (kgf / cm 2 ). The tensile breaking strength in the MD of the PO microporous membrane (MD tensile breaking strength) and the tensile breaking strength in the TD (TD tensile breaking strength) were measured. The ratio (MD strength / TD strength) was also calculated.
[0118] (7) Pore size (μm) In accordance with the half-dry method, the average pore size (μm) of the PO microporous membrane was measured using a perm porometer (Porous Materials, Inc.: CFP-1500AE. As the impregnating liquid, perfluoropolyester (trade name "Galwick", surface tension 15.6 dyn / cm) manufactured by the same company was used. For the dry curve and the wet curve, the applied pressure and the air permeation amount were measured, and from the pressure PHD (Pa) at which the 1 / 2 curve of the obtained dry curve intersects the wet curve, the average pore size dHD (μm) was determined by the following formula, and was defined as the pore size. dHD=2860×γ / PHD
[0119] (7) Thermal shrinkage rate at 105°C (%) The PO microporous membrane was cut to 100 mm in the MD direction and 100 mm in the TD direction, and left to stand in an oven at a predetermined temperature (105°C) for 1 hour. At this time, the sample was sandwiched between two sheets of paper so that hot air did not directly hit the sample. As the paper, V-Paper monochrome copy / printer paper manufactured by Fuji Xerox Interfield (basis weight 64 g / m 2 ) was used. After the sample was taken out of the oven and cooled, the length (mm) was measured, and the thermal shrinkage rate was calculated by the following formula. The measurements were performed in the MD direction and the TD direction respectively. Thermal shrinkage rate (%) = {(100 - Length after heating) / 100} × 100
[0120] (8) Characteristics measured by thermomechanical analysis (TMA) The measurement was performed in the shrinkage stress mode in the MD direction of the PO microporous membrane using TMA60 (trademark) manufactured by Shimadzu Corporation. A sample obtained by cutting the PO microporous membrane into a size of 5 mm in width × 13 mm in length along the MD direction was fixed to chucks such that the distance between the chucks was 10 mm, and set on a tension probe. The initial load was set to 0.01 N, the mode was set to the shrinkage stress mode, the sample was heated from room temperature to 180°C at a temperature elevation rate of 10°C / min, and the load (N) generated at that time was measured. The measured load (N) was divided by the cross-sectional area (mm 2 ) of the PO microporous membrane defined by the film thickness × 5 mm width, to calculate the stress per cross-sectional area (N / mm 2 ) From the shrinkage stress S measured at 140°C as described above 140 (N / mm 2 ), and the maximum shrinkage stress S at a temperature exceeding 140°C max (N / mm 2 ) (the temperature T at the time of S max ), the value of the stress gradient A was calculated from the two points using the following formula max Stress gradient A = (S max - S 140 ) / (T max - 140) Furthermore, the shrinkage stress S at 100°C measured above... 100 (N / mm 2 ) and shrinkage stress S at 120°C 120 (N / mm 2 Based on these two points, the value of the stress gradient B was calculated using the following formula. Stress gradient B = (S 120 -S 100 ) / (120-100) Furthermore, in the measurement using the above shrinkage stress mode, the temperature at which the load above 140°C showed 0N when heated (the temperature at the moment the load was completely released) was defined as the film rupture temperature (°C).
[0121] [Example 1] Table 1 shows polyethylene (PE2, Mv=3,170,000, density 0.93 g / cm³). 3 Polyethylene (PE1, Mv=1,160,000, density 0.94 g / cm³) and liquid paraffin (LP) were mixed in a mass ratio of PE2:LP=10:90 (mass%) and subjected to micronization treatment using a high-pressure homogenizer. The results are shown in Table 1. 3 The ) were mixed in a Henschel mixer, and then an appropriate amount of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant and pre-mixed. The above-mentioned atomized mixture was supplied to the feed ports of a twin-screw extruder using a quantitative supply pump, and the pre-mixed resin was supplied using a feeder. At this time, the amount supplied to the extruder was adjusted so that the mass ratio of PE1:PE2 was the raw material composition ratio shown in Table 2. Furthermore, liquid paraffin (LP) was added to the twin-screw extruder cylinder in two separate additions via side feed so that the ratio of liquid paraffin (LP) in the total mixture extruded after melt-kneading was the raw material composition ratio shown in Table 2, taking into account the amount of LP added in the above atomization treatment. The set temperatures were 160°C for the kneading section and 200°C for the T-die. Next, the molten mixture was extruded into a sheet shape from a T-die and cooled with a cooling roll controlled to a surface temperature of 70°C to obtain a sheet-like molded product with a thickness of 1200 μm.
[0122] The obtained sheet-like molded material was guided into a simultaneous biaxial stretching machine to obtain a primary stretched film (primary stretching step). The set stretching conditions were an MD stretching ratio of 7x, a TD stretching ratio of 6.38x, and an MD and TD stretching temperature of 115°C. Next, the obtained primary stretched film was guided into a methylene chloride bath and thoroughly immersed to extract and remove the liquid paraffin, which is a plasticizer, and then the methylene chloride was dried off to obtain an extracted film.
[0123] Next, the extracted film was guided to a TD uniaxial tenter for heat fixation. For the heat fixation process, stretching was performed under conditions of a TD stretching temperature of 133°C and a TD stretching ratio of 1.97, followed by relaxation under conditions of a relaxation temperature of 133°C and a relaxation ratio of 0.81. Various properties of the obtained PO microporous film were evaluated using the above method. The film formation conditions are shown in Table 2, and the results are shown in Table 3. Furthermore, a schematic diagram of the measured shrinkage stress of the TMA of the obtained PO microporous film at MD is shown in Figure 1.
[0124] [Examples 2-6] A PO microporous film was obtained in the same manner as in Example 1, except that the raw material type, raw material composition ratio, stretching process conditions, and heat setting process conditions were set as shown in Table 1 or Table 2, respectively. Various properties of the obtained PO microporous film were evaluated using the method described above. The results are shown in Table 3.
[0125] [Examples 7-9, Comparative Example 6] A PO microporous membrane was obtained in the same manner as in Example 1, except that polyethylene (PE2) and liquid paraffin (LP) were mixed in a mass ratio of PE2:LP = 18:82 (mass%), and the mixture was subjected to a microatomicization process using a high-pressure homogenizer, with the raw material type, raw material composition ratio, stretching process conditions, and heat setting process conditions set as shown in Table 1 or Table 2. Various properties of the obtained PO microporous membrane were evaluated using the method described above. The results are shown in Table 3.
[0126] [Example 10] A PO microporous membrane was obtained in the same manner as in Example 1, except that polyethylene (PE2) and liquid paraffin (LP) were mixed in a mass ratio of PE2:LP = 18:82 (mass%), subjected to micronization treatment in a high-pressure homogenizer, and then an appropriate amount of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant and pre-mixed, and the mixture was supplied to the feed port of a twin-screw extruder using a quantitative supply pump. Various properties of the obtained PO microporous membrane were evaluated using the above method. The results are shown in Table 3.
[0127] [Comparative Examples 1-5] The PE types and raw material composition ratios shown in Tables 1 and 2 were mixed in a Henschel mixer, and an appropriate amount of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant and pre-mixed. The resulting mixture was supplied to the feed port of a twin-screw coaxial screw extruder via a feeder. Liquid paraffin (LP) was added to the twin-screw extruder cylinder in two separate stages via side feed so that the ratio of liquid paraffin to the total mixture extruded after melt-kneading would match the raw material composition ratio shown in Table 2. A PO microporous membrane was obtained in the same manner as in Example 1, except that the stretching and heat-setting process conditions were set as shown in Table 2. Various properties of the obtained PO microporous membrane were evaluated using the above method. The results are shown in Table 3. A schematic diagram of the measurement results of the shrinkage stress at MD of the TMA of the PO microporous membrane obtained in Comparative Example 1 is shown in Figure 2.
[0128] [Table 1]
[0129] [Table 2-1]
[0130] [Table 2-2]
[0131] [Table 3-1]
[0132] [Table 3-2]
[0133] As is clear from the results in Table 3, PO microporous membranes that satisfy the following conditions: viscosity-average molecular weight (Mv) of 1,200,000 or more, average pore diameter of 0.020 μm or more, and stress gradient A value of 0.070 or less, exhibit high basis weight equivalent puncture strength (gf / (g / m²). 2 )), low air permeability (seconds / (100cm) 3 It was possible to achieve a high degree of compatibility between a thickness of 10 μm and a low thermal shrinkage rate (%).
Claims
1. A polyolefin microporous membrane containing polyethylene as the main component, The viscosity-average molecular weight (Mv) of the polyolefin microporous membrane is 1,200,000 or more and 9,000,000 or less. The average pore size measured according to the half-dry method for the aforementioned polyolefin microporous membrane is 0.020 μm or more and 0.100 μm or less, and The shrinkage stress S at 140°C was measured by the shrinkage stress mode in the MD of thermomechanical analysis (TMA) of the aforementioned polyolefin microporous membrane. 140 And the maximum shrinkage stress S at temperatures above 140°C max A polyolefin microporous membrane in which the stress gradient A, calculated from the two points, is between 0.030 and 0.
070.
2. The polyolefin microporous membrane according to claim 1, wherein, in the molecular weight distribution curve of the polyolefin microporous membrane obtained by gel permeation chromatography (GPC) measurement, the ratio of components with a molecular weight of 300,000 or less to the total molecular weight components is 10% by mass or more and 45% by mass or less, and the ratio of components with a molecular weight of 3,000,000 or more is 2% by mass or more and 30% by mass or less.
3. The maximum shrinkage stress S at temperatures above 140°C was measured by the shrinkage stress mode in the thermomechanical analysis (TMA) of the aforementioned polyolefin microporous membrane. max 2.0 N / mm 2 The polyolefin microporous membrane according to claim 1, which is as follows:
4. The shrinkage stress S at 100°C was measured by the shrinkage stress mode in the thermomechanical analysis (TMA) of the aforementioned polyolefin microporous membrane. 100 And, the shrinkage stress S at 120°C 120 The polyolefin microporous membrane according to claim 1, wherein the value of the stress gradient B calculated from the two points is -0.010 or more and 0.010 or less.
5. The polyolefin microporous membrane according to claim 1, wherein the rupture temperature, as measured by the shrinkage stress mode in thermomechanical analysis (TMA) of the polyolefin microporous membrane, is 150°C or higher and 240°C or lower.
6. The polyolefin microporous membrane according to claim 1, wherein the porosity of the polyolefin microporous membrane is 20% or more and 50% or less.
7. The MD tensile strength and TD tensile strength of the aforementioned polyolefin microporous membrane are both 2000 kgf / cm². 2 The polyolefin microporous membrane described in claim 1 is as described above.
8. The polyolefin microporous membrane according to claim 1, wherein the ratio of the MD tensile breaking strength to the TD tensile breaking strength (MD strength / TD strength) of the polyolefin microporous membrane is 0.3 or more and 3.0 or less.
9. The polyolefin microporous membrane according to claim 1, wherein the thickness of the polyolefin microporous membrane is 10 μm or less.
10. A separator for electrochemical devices comprising a polyolefin microporous membrane according to any one of claims 1 to 9.
11. An electrochemical device comprising the separator for an electrochemical device described in claim 10.
12. A mixing step (a) in which a resin composition containing a polyolefin resin and a pore-forming material is mixed, The mixture obtained in step (a) is melted and kneaded and then extruded in extrusion step (b), The sheet forming process (c) involves forming the extruded material obtained in process (b) into a sheet, The sheet-like molded product obtained in step (c) is stretched at least once in at least one axial direction in a primary stretching step (d), Extraction step (e) is performed to extract the pore-forming material from the primary stretched film obtained in step (d), The heat-fixing step (f) involves heat-fixing (HS) the extracted film obtained in step (e) and A method for producing a polyolefin microporous membrane containing, A method for producing a polyolefin microporous film, characterized in that step (a) includes a process of atomizing the polyolefin resin either alone or, if the pore-forming material is a liquid plasticizer, in a mixed state with the liquid plasticizer.
13. The method for producing a polyolefin microporous membrane according to claim 12, wherein the polyolefin resin includes ultra-high molecular weight polyethylene.
14. In step (d), the sheet-like molded material is stretched to MD and TD. After step (e), the extracted film is heat-fixed to the TD in step (f). A method for producing a polyolefin microporous membrane according to claim 12 or 13.
Citation Information
Patent Citations
High intensity separator
JP2023120223A
Polyolefin microporous membrane
WO2020256138A1